PROTOTYPE ORGANISASI CILIK MOHAMAD AMIN (OSCIMA) SANTRI TAMAN PENDIDIKAN AL-QUR’AN (TPQ) MOHAMAD AMIN DARUNNAJAH 15 KOTA BENGKULU ( STUDI KASUS MEMBENTUK KEMAMPUAN ORGANISASI - Prayudha, Aryo Ihsan; Palenti, Citra Dwi; Gusti, Ririn (Comm-Edu (Community Education Journal), 2025)
This study aims to describe the prototype of the Student Leadership Program at TPQ Mohamad Amin Darunnajah 15 in Bengkulu City. This program is designed to shape the character, communication skills, and organizational abilities of students through a comprehensive educational approach. The method used is a qualitative case study with interviews with the TPQ principal, ustadz, and ustadzah. The results of the study indicate that the program has been running, but is not yet structured. The program focuses not only on academic aspects, but also on moral development, memorization (tahfidz), fiqh, Arabic language, tajwid, and public speaking. The program faces challenges such as low public and parental awareness of the importance of religious education, as well as student fatigue due to the density of formal school activities. The program's success is supported by collaboration between teachers and parental support. Regular sharing and guidance activities help students manage emotions and share experiences. Researchers have designed an initial model of the program that has reached the stage of forming a student organizational structure (OSCIMA), oriented towards character, communication, and social-emotional skills. This study recommends improving the quality of mentoring for teachers and regular evaluation for more optimal program development.